The STIM1-binding site nexus remotely controls Orai1 channel gating - Zhou, Yandong (Nat Commun, 2016)
The ubiquitously expressed Orai Ca(2+) channels are gated through a unique process of intermembrane coupling with the Ca(2+)-sensing STIM proteins. Despite the significance of Orai1-mediated Ca(2+) signals, how gating of Orai1 is triggered by STIM1 remains unknown. A widely held gating model invokes STIM1 binding directly to Orai1 pore-forming helix. Here we report that an Orai1 C-terminal STIM1-binding site, situated far from the N-terminal pore helix, alone provides the trigger that is necessary and sufficient for channel gating. We identify a critical ‘nexus' within Orai1 connecting the peripheral C-terminal STIM1-binding site to the Orai1 core helices. Mutation of the nexus transforms Orai1 into a persistently open state exactly mimicking the action of STIM1. We suggest that the Orai1 nexus transduces the STIM1-binding signal through a conformational change in the inner core helices, and that STIM1 remotely gates the Orai1 channel without the necessity for direct STIM1 contact with the pore-forming helix.